Electrospun poly(L-Lactic Acid) nanofibres loaded with Dexamethasone to induce osteogenic differentiation of human mesenchymal stem cells - Nguyen, Luong T. H. (2013)
Dexamethasone (Dex), a synthetic corticosteroid, was loaded into poly(L-lactic acid) (PLLA) nanofibrous scaffolds with a concentration of 0.333 wt% by electrospinning. The Dex-loaded PLLA nanofibres increased the mechanical strength in comparison with pure PLLA nanofibres. A sustained release profile for over 2 months with an initial burst release after 12 h of 17% was shown. Importantly, the amounts of Dex released from the PLLA nanofibres every 3 days were close to the ones used for the standard osteogenic medium. The sustained osteoinductive environment created by released Dex strongly differentiated human mesenchymal stem cells (hMSCs) cultured in the Ost−Dex medium. ALP activity, BSP expression and calcium deposition were significantly higher than those of the cells cultured on the PLLA scaffolds without Dex. A large amount of hydroxyapatite-like minerals was observed on the Dex-loaded PLLA scaffolds after 21 days culture. The cells on these scaffolds also indicated an osteoblastic morphology on the 14th day. Besides, these scaffolds slightly increased the cell proliferation comparing to the scaffolds without Dex. As such, the PLLA nanofibres loaded with 0.333 wt% Dex was an effective osteoinductive scaffold which acts as a promising strategy for bone treatment.